Dreading Yet Hoping: Traumatic Loss Impacted by Reference DNA Sample Collection for Families of Missing People - Wayland, Sarah; Ward, Jodie (Frontiers in Psychiatry, 2022)
The trauma of having a family member missing is commonly described as an ambiguous loss where the finality of the loss is not realised, as is experienced with a death. There is uncertainty due to the trauma of the absence and subsequent police investigation, leading to physical and emotional impacts for the aftercare of those left behind. There are 850 unidentified human remains and 2,600 long-term missing persons cases in Australia. The Australian Federal Police (AFP) National DNA Program for Unidentified and Missing Persons aims to scientifically link these cases using modern DNA techniques and databases. A DNA-led identification effort may assist to provide answers to Australian families searching for missing relatives, but may also contribute to the trauma experienced by these families. A literature review demonstrated empirical research for the development of scientific best practices for the collection of reference DNA samples for forensic purposes, but minimal evidence about the impact of reference DNA sample collection on kin when attempting to identify the deceased remains of missing people in non-mass casualty situations. The aim of this study was to develop an academically robust understanding of the unique impact of reference DNA sample collection on families of missing persons and support pathways tailored to the experience. This study of 26 families of long-term missing people in Australia identified that the provision of a reference DNA sample may be an overt act of hope, as families perceive their sample assists the investigation, in addition to experiences akin to a traumatic event triggered a missing person requiring scientific matching. The thematic analysis of a qualitative survey about family members’ experiences of providing reference DNA samples to aid missing persons investigations, demonstrate immediate interpersonal impacts and evidence of ongoing impacts to families’ wellbeing. The study concludes that the complexity associated with provision of family reference samples requires the development and implementation of best practice guidelines, including psycho-education strategies to be used by police to minimise the vicarious trauma for relatives already traumatised by the loss of their missing person These guidelines would benefit all routine missing persons investigations.